Sea Trade in Sangam Literature - R, Aishwarya; P, David Prabhakar (International Research Journal of Tamil, 2022)
Literature is a mirror that captures the art, culture, history, life, environment, technology etc. In this way the Sangam literature captures the life, environment, love, heroism, politics and business of the people of that time. This article explains the maritime trade of Sanga Tamizhar and it reveals merchant character, Sangam period port scenery, commercial stations, Palandamizhar exports and imports through Sangam literature. The Sangam period is considered as the golden age of sea trade. It is known from Sangha literary songs that world famous ports were functioning in Chera, Chola and Pandyan countries. It is a well-known news that ancient Tamil people excelled in business. Especially they excelled in maritime trade. In the Sangam literature, Maduraikkanji and Pattinapalai are sources which provide more information about trade during the Sangam period. Tamil people traded across the sea to places like Unjai, Padali (Padalipuram), Kashi, Varanasi, Kalingapatnam and other countries such as Savagam (East Indies), Kaalagam (Burma), Kitaram (Kadaram), Takkola etc. Other nations who traded with Tamil period during the Sangam period were Arabs, Yavanas and Savakas. It can be known with the help of Sanga mliterature that the Chinese did not trade with the Tamil people during that period. Sangam literature mentions that jaggery and sugar made from sugarcane juice, alcohol, pepper, salt, vala (conch), cloth, pearls, wood species, sapphire, ivory (ivory) etc. were exported from Tamil Nadu to other countries during the Sangam period. This article highlights the sea trading of Sangam period.